Optimal operational planning of biomass district heating: Adaptation to air pollution episodes with LCA-based dynamic penalization - Boussaid, Taha; Rousset, François; Scuturici, Vasile-Marian; Clausse, Marc (Energy (Oxford), 2025)
The pervasive impacts of climate change are reshaping both the development of new technologies and the adaptation of existing ones, especially for energy systems. Besides the reduction of their environmental footprint, they must cope with extreme weather events. However, for this large-scale system, the adaptation to new climate events is subject to several operational constraints and economic challenges. In this work, the adaptation of a common configuration of French district heating networks is evaluated. The energy portfolio consists of biomass, waste incineration, gas and thermal energy storage. We examine how the system can be adapted to face pollution peaks of particulate matter during anticyclonic events that occur during the heating season in France. A novel dynamic penalization for pollutant emissions from biomass boilers is derived from its variable load operation. It is then used in a multicriteria planning optimization. This approach provides a new perspective to manage emissions during air pollution peaks, an area that has not been thoroughly explored in district heating adaptation strategies. The results show that the network is able to avoid using biomass at low loads during pollution episodes against a slight increase of 2.1% in the operational costs. In addition to performing life cycle impact assessment, the relevance of our approach is tested by comparing different penalization formulations and by varying the thermal energy storage capacity. •Optimal planning of a district heating with regard to environmental impacts.•A novel dynamic penalization is applied to avoid high pollutant emissions.•The planning effectively avoids using biomass boiler at low loads during pollution episodes.•The thermal storage is used in a more dynamic way to unlock more flexibility.